Role of Lipocalin-2 in Thrombin-induced Brain Injury - Mao, Shanshan (Stroke, 2016)
BACKGROUND AND PURPOSE: Thrombin and lipocalin-2 (LCN2) contribute to intracerebral hemorrhage-induced brain injury. Thrombin-induced brain damage is partially through a thrombin receptor, protease-activated receptor-1 (PAR-1). LCN2 is involved in cellular iron transport and neuroinflammation. The present study investigated the role of LCN2 in thrombin-induced brain injury. METHODS: There was three parts in this study. First, male adult C57BL/6 wild type (WT) or LCN2 knockout (LCN2 KO) mice had an intracaudate injection of thrombin (0.4U) or saline. Second, LCN2 KO mice had an injection of thrombin (0.4U) with recombinant mouse LCN2 protein (1µg) into the right caudate. Third, PAR-1 KO or WT mice had an intracaudate injection of thrombin or saline. All mice had T2-weighted magnetic resonance imaging and behavioral tests. Brains were used for histology, immunohistochemistry and Western blotting. RESULTS: Intracerebral thrombin injection caused LCN2 upregulation and brain injury in mice. Thrombin-induced brain swelling, blood-brain barrier disruption, neuronal death and neurologic deficits were markedly less in LCN2 KO mice (p<0.05) and were exacerbated by exogenous LCN2 co-injection. In addition, thrombin injection resulted in less LCN2 expression and brain injury in PAR-1 KO mice. CONCLUSIONS: Thrombin upregulates LCN2 through PAR-1 activation and causes brain damage.